User Customizable Interaction in Coexistence Space - Kim, KangGeon; Park Myoung Soo; PARK, JUNG MIN (2014 11TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2014)
This paper proposes a user customizable interface for user-centered interaction in a space where the real, virtual and remote world is unified and indistinguishable through a combination of humans, artifacts and a virtual world. We have developed a new user customizable interface, which is a set according to the preferences of users and is intuitive and natural to minimize inconvenience of using the dedicated interface. We have executed several experiments using user gestural expression as user customizable interface such as: various devices control, object handling, environmental interaction, and command transmission in the space. The results of the demonstration have shown that effective interaction with a user customizable interface is possible among the real, virtual and remote worlds.
Keywords: User Customizable Interface; Coexistence Interaction; Gesture Recognition